Rodent burrows in chernozems as a paleoarchive of vegetation dynamics: A case study from the central chernozem region of Russia - Pimenov, Valerii E.; Ponomarenko, Elena V.; Chendev, Yury G.; Ershova, Ekaterina G.; Dergacheva, Maria I.; Smirnova, Maria A. (Geoderma Regional, 2025)
Northern сhernozems are formed at the interface of the steppe zone with broadleaved forests. Boundaries between these ecosystems were shifting in the Holocene, following changes in climate and land use practices. It is expected that modern chernozemic soils went through multiple stages of development under various plant formations that altered soil properties, but reconstruction of vegetation dynamics in the steppe region is limited by a scarcity of paleoecological archives, such as peatlands and lakes. Zooturbation is the hallmark of arid regions; it results in the formation of infilled burrows — krotovinas, that are numerous and ubiquitous in chernozems. In northern steppes most krotovinas are created by the greater mole-rat (Spalax microphthalmus). Infill of vertical shafts of krotovinas varies in color and humus content within one soil profile, suggesting that they have been formed over a considerable timespan. We analyzed pollen composition of the vertical krotovinas and compared it to pollen spectra of surficial horizons in chernozems of northern steppes. All krotovinas contained pollen of the quantity and preservation degree that enabled vegetation reconstruction. Surface pollen spectra reflected disturbed meadow-steppe vegetation, whereas pollen spectra of krotovinas varied from those of forested to dry steppe communities. Ordination of pollen spectra from krotovinas according to their humus content suggests major successions in vegetation cover from Artemisia-dominated xerophytic ecosystems to wet, warm-climate meadow-steppes affected by fires and pastoralism, and further to more forested landscapes. The results show that infilled vertical burrow shafts of steppe rodents can be used as a paleoecological archive similar to paleosols. •Vertical krotovinas in Chernozems are used as a paleoenvironmental archive.•Pollen spectra of vertical krotovinas reflect past vegetation and climate variability.•Ground-nesting bees influence soil pollen composition.•Spectrum correction for “bee taxa” refines climate and vegetation reconstruction.